УКРАЇНСЬКА ЛІТЕРАТУРА В ЗАГАЛЬНІЙ СТРУКТУРІ КУЛЬТУРНОГО ПРОЦЕСУ: РАННІЙ МОДЕРНІЗМ (Zaporizhzhia Historical Review, 2021)
The Ukrainian literature in the general structure of the cultural process: the early modernism. The article is dedicated to the features of the early Ukrainian modernism in connection with the immanent tendencies of the national and cultural development.